Comparative and Contrastive Analysis of the Peculiarities of the National Character in English and Uzbek Proverbs - Abdurasulovna, Makhsudova Nilufar; Botiraliyevna, Bakirova Khilolakhon; Demirbilek, Mine (Indonesian Journal Publisher, 2024)
This article is devoted to the comparative and contrastive analysis of the peculiarities of the national character of English and Uzbek people in the paremiological picture world. It is known that the comparison and contrast of English and Uzbek paremiological units make it possible to identify similar and different features of the spiritual world and the national identity of people belonging to two ethnic communities. In this study, about 3000 English and Uzbek proverbs and sayings have been analyzed. Based on them general and specific features of the English and Uzbek national character have been determined.